Memoria unei limbi vorbite cu vinovăție - Gina Aurora NECULA (ACROSS)
From its transformation into a taboo and its hiding under the so-called “Moldovan language” or under the euphemistic expression “state language”, to its regained status recognition as an official language, the Romanian language spoken in the Republic of Moldova has undergone impressive reforms in the last 60 years. Meant to erase the awareness of citizens’ ethnic identity and turn a majority language into a minority one, all the laws and regulations issued on the field succeeded in setting numerous barriers for speakers of Romanian in the Republic of Moldova. Either manifested as social constraints or materialized into an assumed rejection of mother tongue usage, all these laws have demonstrated their usefulness and major impact on the Romanian-speaking population. This article is the result of our research carried out over 10 years with the support of students, Moldovan citizens, from the master's degree program "Romanian Language - Identity and Cultural Awareness". Our analysis shows that although the status of the Romanian language in the Republic of Moldova has changed, making the official leap from ”ethnic language” to official state language, speakers still use it with the fear that they are not speaking it correctly and that they might be in danger of using structures that are inappropriate for the Romanian language because that they have many years of experience in using the Russian language as lingua franca. In this paper, we provide arguments to demonstrate the evolution of the Romanian language spoken in Moldova, despite all the social and political barriers imposed over time.